1993
DOI: 10.2337/diab.42.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypoxia on Insulin Secretion by Isolated Rat and Canine Islets of Langerhans

Abstract: The effect of pO2s reduced below physiological levels on GSIR by isolated islets of Langerhans was investigated with a microperifusion apparatus that provided control of pO2 and rapid dynamic response. Second-phase insulin secretion was reduced substantially by hypoxia. The response to lower pO2 was rapid and reversible. Although the steady, normoxic (pO2 = 142 mmHg) second-phase secretion rate varied widely from one islet preparation to another, the ratio of Sx to S142 for each preparation could be represente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
209
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(218 citation statements)
references
References 0 publications
7
209
1
1
Order By: Relevance
“…Low beta cell survival and abnormal insulin release from pancreatic beta cells exposed to hypoxia have been extensively studied and found in different mammalian species (Dionne et al 1993;Moritz et al 2002;Lai et al 2009). Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Low beta cell survival and abnormal insulin release from pancreatic beta cells exposed to hypoxia have been extensively studied and found in different mammalian species (Dionne et al 1993;Moritz et al 2002;Lai et al 2009). Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, clinical trials show that long-term outcomes of islet transplantation are hampered by rejection, which lead to a gradual decrease in islet function usually taking place over the first years after transplantation (Shapiro et al 2006). One of the major factors of beta cell destruction after islet transplantation is the markedly decreased oxygen tension in the implantation sites and the high susceptibility of beta cells to hypoxia (Carlsson et al 2001;Dionne et al 1993). Recently, it was also shown that alteration of islet cell organization and impaired glucose sensing mechanisms may be induced by activation of hypoxia inducible factor-1a by deletion of the Vhlh gene codes for the von Hippel-Lindau protein that is a key player in the cellular response to oxygen sensing (Puri et al 2009;Cantley et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We now understand that to ensure a better nutrient and oxygen supply to encapsulated islets, the distance between islets and the vasculature should be kept to a minimum. In vascularised tissue, the maximum distance for an effective diffusion of oxygen and nutrients from capillary to cells is 200 mm [47][48][49][50]. Because there is no convection movement within a capsule, the only driving force for the transfer of nutrients to islet cells is the concentration gradient.…”
Section: Size and Smoothness Of Microcapsulesmentioning
confidence: 99%
“…In addition, activation of HIF-1a reduces glucose uptake and changes aerobic glucose metabolism to anaerobic glycolysis. During isolation and early post-transplantation, providing oxygen solely by gradient-driven passive diffusion results in decreasing oxygen pressure in islets radially from the periphery to the core (131). Different strategies suggested to overcome the hypoxia challenge include hyperbaric oxygen (HBO) therapy (132), design of gas permeable devices (133), oxygen carrier agents (134) and in situ oxygen generators (135).…”
Section: Oxygen Delivery To the Isletsmentioning
confidence: 99%